Analisis Minat Penggunaan pada Fitur Pembelian Mobile Banking BSI: Pendekatan TAM dan TPB - Sodik, Fajar; Nur Zaida, Alifia; Zulmiati, Khusnul (UIN Sunan Kalijaga Yogyakarta, 2022)
Research Aims: Today's rapid technological development is a means for the banking industry to increase digital transactions. Bank Syariah Indonesia as one of the banking industries that was formed from the merger of three state-owned Islamic banks has also begun to develop a digital financial transaction system through its mobile banking services. In this study, the focus of the researcher refers to the purchase feature where the feature is already widely known and used by the wider community. The purpose of this study is to analyze the factors that influence the interest in using the purchase feature through the acceptance of the technology used in service mobile banking BSI's. Design/methodology/approach: The method used in this study is a quantitative method. Data collection was done by distributing questionnaires to respondents using purposive sampling technique. Respondents in this study were students and the general public who were both customers and users of mobile banking BSI's. The data analysis technique was carried out using the technique Structural Equation Modeling (SEM)through the Warp PLS 5.0 analysis tool. Reseach Findings: The results of the SEM analysis show that there is good interest in customers who use the purchase feature of mobile banking BSI's. The existence of this feature also makes it easier for customers to carry out each financial transaction and increases effectiveness and productivity. Research limitation and implication: The implications of this research are expected to be input for practitioners who take part in the Islamic banking industry to improve service quality to meet customer needs in terms of digital financial transactions.